Atypical neuroleptic malignant syndrome. “Doing more harm than gain” - Bhat, Khalid Javid; Pandita, Kamal Kishore; Bhat, Sanjay; Gupta, Subhash Chander (International Journal of Research in Medical Sciences, 2017)
Neuroleptic malignant syndrome (NMS) a rare, idiosyncratic, and potentially fatal adverse reaction can be deceptive especially when the hallmark features are lacking. Most diagnostic criteria include fever and muscle rigidity, although NMS may present without either. Delirium, agitation and catatonia can be the earliest features of NMS and in acute care settings, concomitant use of sedatives and anti-psychotics by the attending clinicians may even obscure the sentinel signs of NMS and further aggravate the underlying insult. A strong clinical suspicion based on clinical history is crucial for early diagnosis and treatment and the strict adherence to the classical criteria of NMS may lead to a diagnostic delay and dire consequences for these patients and sometimes this delay can procure death.